Images and Spectra of the 2017 Total Solar Eclipse Corona From Our Oregon Site - Pasachoff, Jay M.; Lockwood, Christian; Meadors, Erin; Yu, Ross; Perez, Cielo; Peñaloza-Murillo, Marcos A.; Seaton, Daniel B.; Voulgaris, Aris; Dantowitz, Ron; Rušin, Vojtech; Economou, Thanasis (Frontiers in Astronomy and Space Sciences, 2018)
Abstract We report on early results from a suite of instruments for imaging and spectra we deployed to Salem, Oregon, for two minutes of totality at the August 21, 2017, total solar eclipse. Our instruments included refracting telescopes and telephoto lenses for use with CCD detectors and DSLR cameras, narrow-band filters at the wavelengths of coronal emission lines ([Fe XIV] 530.3 nm and [Fe X] 637.4 nm), and spectrographs. We also monitored the effect of the eclipse penumbra and umbra on the terrestrial atmosphere.